Comparative study on addition of carbon fiber in concrete with partial replacement of demolished concrete waste in structural concrete. (2020) - Sathish, T.; Palanikumar, B.; Karthick, S.
Abstract: A significant amount of construction waste has been continuously increased in the last decades and environmental concerns on the recycling of the demolition waste have consequently been increased. This research, concrete waste is from demolished structure has been collected and the coarse aggregate of optimum percentage is used for preparing fresh concrete. This experimental investigation was performed to evaluate the strength of concrete, in which natural aggregate was partially replaced by with recycled coarse aggregate. The percentages of fiber were added with respect to weight of cement. Tests were performed for 20% of replacement of aggregate by RCA with various percentages of (0%, 0.2%, 0.4%, 0.6%, 0.8%, 1%) of carbon fiber.